BIOSTRATIGRAPHIC CORRELATION OF PALEOZOIC ROCKS IN NORTHERN AND WESTREN IRAQ - Al-jubori, Falah H. Khalaf; Youkhana, Akram K.; Naqshabandi, Srood F.; Bayz, Dyana A. (International Journal of Research -GRANTHAALAYAH, 2020)
The Paleozoic rocks outcropped in northern Iraq (Ora, Chia Zairi section) are biostratigraphically investigated for their microfossils content. Benthonic foraminifera and algal genera characterize the upper part of the section while palynomorphs (Miospores & Acritarchs) dominated the lower part the section which is consist of clastic sediments. The study also include the stratigraphic succession of the section and its correlation to the subsurface sections penetrated in oil and water wells drilled in the western desert of Iraq in order to determine the regional distribution of the economically important formations, either as reservoir or as source rocks for hydrocarbons. Index palynomorphs including many types of Acritarch genera are identified in the Khabour Formation indicate lower Ordovician time (Tremadocian? Arenigian –Llanvirnian: age) The Perispik Formation has been found barren of any type of microfossils and is composed of red clastic rocks. Pollen and Spores are recorded from the "Ore Group" (Kaista, Ora and Harur Formations ) indicate that these rocks are of Upper Devonian – Lower Carboniferous (Famennian – Tournaisian age ) .A Large number of foraminifera and Algal genera are identified in the Chiazairi rocks,these genera and species are indicated the Upper Permian rocks of Thuringian age. The stratigraphic succession of the Paleozoic section studied in northern Iraq indicate that there is a stratigraphic break represents by missing of the Ga’ara Formation (late Carboniferous –early Permian) and Akkas Formation (Silurian) and the upper part of the Khabour Formation (Upper Ordovician).